Looking the Other Way: The Impact of Reclassifying Cannabis on Police Warnings, Arrests and Informal Action in England and Wales - Warburton, Hamish (The British journal of criminology, 2005)
British drugs legislation has recently been changed to reclassify cannabis from a Class B drug to a Class C one. The reclassification is intended to reflect more accurately the risks posed by cannabis relative to other drugs. The debate about reform of the British laws in regulating cannabis possession has tended to ignore the fact that even before cannabis was reclassified as a Class C drug, police officers often turned a blind eye' to cannabis offences, or else gave informal warnings. This paper examines the political background to reclassification. It then examines the factors that guide officers to use their discretion and informally dispose of cannabis offences. It goes on to consider the impact that reclassification may have on informal action. The data are drawn from a detailed study of the policing of cannabis prior to reclassification, conducted by the Institute for Criminal Policy Research.1 We demonstrate that a multiplicity of police, offender and situational factors, either alone or in combination, influence an officer's decision to take informal action on the street. We outline the potential for reclassification to generate a reduction in the use of informal disposals, which may create a net-widening' effect, or an increase in use, which might lead to the offence being selectively decriminalized. The implications for both scenarios are considered